Women’s History in Education in the United States - Audrey Dentith (Adult Education Research Conference, 2016)
The history of women’s education in the United States is a rich and colorful one, marked by struggle and victory against huge odds. This roundtable paper, a work in progress, highlights the remarkable efforts of specific women to achieve the right to an education for all women from the end of the Revolutionary War through the 1990s.
Keywords: women& #x27; s education; history